Answer:
![y = -6(x - \frac{1}{2})^2 -\frac{7}{2}](https://tex.z-dn.net/?f=y%20%20%3D%20-6%28x%20-%20%5Cfrac%7B1%7D%7B2%7D%29%5E2%20-%5Cfrac%7B7%7D%7B2%7D)
Step-by-step explanation:
Given:
![y = -6x^2 + 3x + 2](https://tex.z-dn.net/?f=y%20%3D%20-6x%5E2%20%2B%203x%20%2B%202)
Required
Rewrite in vertex form
The vertex form of an equation is in form of: ![y = a(x - h)^2+ k](https://tex.z-dn.net/?f=y%20%3D%20a%28x%20-%20h%29%5E2%2B%20k)
Solving: ![y = -6x^2 + 3x + 2](https://tex.z-dn.net/?f=y%20%3D%20-6x%5E2%20%2B%203x%20%2B%202)
Subtract 2 from both sides
![y - 2 = -6x^2 + 3x + 2 - 2](https://tex.z-dn.net/?f=y%20-%202%20%3D%20-6x%5E2%20%2B%203x%20%2B%202%20-%202)
![y - 2 = -6x^2 + 3x](https://tex.z-dn.net/?f=y%20-%202%20%3D%20-6x%5E2%20%2B%203x)
Factorize expression on the right hand side by dividing through by the coefficient of x²
![y - 2 = -6(x^2 - \frac{3x}{6})](https://tex.z-dn.net/?f=y%20-%202%20%3D%20-6%28x%5E2%20-%20%5Cfrac%7B3x%7D%7B6%7D%29)
![y - 2 = -6(x^2 - \frac{x}{2})](https://tex.z-dn.net/?f=y%20-%202%20%3D%20-6%28x%5E2%20-%20%5Cfrac%7Bx%7D%7B2%7D%29)
Get a perfect square of coefficient of x; then add to both sides
------------------------------------------------------------------------------------
<em>Rough work</em>
The coefficient of x is ![\frac{-1}{2}](https://tex.z-dn.net/?f=%5Cfrac%7B-1%7D%7B2%7D)
It's square is ![(\frac{-1}{2})^2 = \frac{1}{4}](https://tex.z-dn.net/?f=%28%5Cfrac%7B-1%7D%7B2%7D%29%5E2%20%3D%20%5Cfrac%7B1%7D%7B4%7D)
Adding inside the bracket of
to give: ![-6(x^2 - \frac{x}{2} + \frac{1}{4})](https://tex.z-dn.net/?f=-6%28x%5E2%20-%20%5Cfrac%7Bx%7D%7B2%7D%20%2B%20%5Cfrac%7B1%7D%7B4%7D%29)
To balance the equation, the same expression must be added to the other side of the equation;
Equivalent expression is: ![-6(\frac{1}{4})](https://tex.z-dn.net/?f=-6%28%5Cfrac%7B1%7D%7B4%7D%29)
------------------------------------------------------------------------------------
The expression becomes
![y - 2 -6(\frac{1}{4})= -6(x^2 - \frac{x}{2} + \frac{1}{4})](https://tex.z-dn.net/?f=y%20-%202%20-6%28%5Cfrac%7B1%7D%7B4%7D%29%3D%20-6%28x%5E2%20-%20%5Cfrac%7Bx%7D%7B2%7D%20%2B%20%5Cfrac%7B1%7D%7B4%7D%29)
![y - 2 -\frac{6}{4}= -6(x^2 - \frac{x}{2} + \frac{1}{4})](https://tex.z-dn.net/?f=y%20-%202%20-%5Cfrac%7B6%7D%7B4%7D%3D%20-6%28x%5E2%20-%20%5Cfrac%7Bx%7D%7B2%7D%20%2B%20%5Cfrac%7B1%7D%7B4%7D%29)
![y - 2 -\frac{3}{2}= -6(x^2 - \frac{x}{2} + \frac{1}{4})](https://tex.z-dn.net/?f=y%20-%202%20-%5Cfrac%7B3%7D%7B2%7D%3D%20-6%28x%5E2%20-%20%5Cfrac%7Bx%7D%7B2%7D%20%2B%20%5Cfrac%7B1%7D%7B4%7D%29)
Factorize the expression on the right hand side
![y - 2 -\frac{3}{2}= -6(x - \frac{1}{2})^2](https://tex.z-dn.net/?f=y%20-%202%20-%5Cfrac%7B3%7D%7B2%7D%3D%20-6%28x%20-%20%5Cfrac%7B1%7D%7B2%7D%29%5E2)
![y - (2 +\frac{3}{2})= -6(x - \frac{1}{2})^2](https://tex.z-dn.net/?f=y%20-%20%282%20%2B%5Cfrac%7B3%7D%7B2%7D%29%3D%20-6%28x%20-%20%5Cfrac%7B1%7D%7B2%7D%29%5E2)
![y - (\frac{4+3}{2})= -6(x - \frac{1}{2})^2](https://tex.z-dn.net/?f=y%20-%20%28%5Cfrac%7B4%2B3%7D%7B2%7D%29%3D%20-6%28x%20-%20%5Cfrac%7B1%7D%7B2%7D%29%5E2)
![y - (\frac{7}{2})= -6(x - \frac{1}{2})^2](https://tex.z-dn.net/?f=y%20-%20%28%5Cfrac%7B7%7D%7B2%7D%29%3D%20-6%28x%20-%20%5Cfrac%7B1%7D%7B2%7D%29%5E2)
![y +\frac{7}{2} = -6(x - \frac{1}{2})^2](https://tex.z-dn.net/?f=y%20%20%2B%5Cfrac%7B7%7D%7B2%7D%20%3D%20-6%28x%20-%20%5Cfrac%7B1%7D%7B2%7D%29%5E2)
Make y the subject of formula
![y = -6(x - \frac{1}{2})^2 -\frac{7}{2}](https://tex.z-dn.net/?f=y%20%20%3D%20-6%28x%20-%20%5Cfrac%7B1%7D%7B2%7D%29%5E2%20-%5Cfrac%7B7%7D%7B2%7D)
<em>Solved</em>